Multimedia Murals for the Collaborative Work with Students of an Online Master’s Degree - Arenas Arredondo, Amilcar Antonio (2023)
The creation of online graduate study programs has spread due to the advance of Information and Communication Technologies (ICTs). In the virtual modality, the achievement of meaningful learning is based on the effective use of the different tools offered by the web. The experience presented here describes the results of a good practice aimed at fostering the collaborative work among the students of the Master’s degree in Computer Mediated Learning of the Pontifical Catholic University of Ecuador through the use of multimedia murals generated in different technological tools. It was applied to four courses (subjects) with a total of 226 students belonging to the first and second levels during the years 2021 and 2022. The teaching methodology implemented matches that of the “flipped classroom.” To conclude, it can be stated that the use of these resources turned out to be a great support to the development of the videoclasses because it favors collaborative learning and helps build knowledge on the web.